Cost Utility of Adjuvant and Neo-Adjuvant Treatment for Breast Cancer: A Systematic Review of Observational Economic Evaluations Study - Luh Putu Febryana Larasanty; Irfanianta Arif Setyawan; Diah Nurlita (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
This study aimed to perform a systematic review of an observational cost-utility analysis of adjuvant and neo-adjuvant agents in breast cancer patients. The PRISMA flowchart was used to conduct the literature search and study selection. Through the use of two databases, PubMed and Scopus, a literature search was done. The eligible study was determined based on the established inclusion criteria. To evaluate the quality of the study, Drummond's checklist was used. Data extraction was conducted to assess characteristics, study perspective, cost and outcome measurement, the cost-utility ratio in ICER value, threshold, sensitivity or probability analysis, and the conclusion of the cost-utility study. There was a total of 7 studies included for review. Four studies compared chemotherapy regimens as adjuvant or neoadjuvant and three studies included hormone therapy or targeted therapy as an intervention that compared. Observational characteristic includes the use of cohort methods, and a large number of participants, the comparison is mostly for adjuvant therapy purposes and direct medical cost measured from a payer perspective. Anthracycline-based chemotherapy like the FAC regimen showed potential cost-effectiveness results. The use of targeted therapy (pertuzumab, trastuzumab) and hormonal therapy (goserelin) is associated with better utility outcomes and an increase in cost burden from intervention. Based to the reviewed studies, anthracycline-containing regimens such as FAC may have pharmacoeconomic properties as adjuvant or neo-adjuvant therapy. While the use of the most recent pharmacological drug has the potential to improve utility outcomes, but is associated with an increase in the intervention's cost burden.